Net-Zero Carbon Communities: A Systematic Bibliometric Review of Research Trends, Structural Gaps, and Future Directions - Chai, Jia Xin; Guo, Ru (Journal of Research in Science and Engineering, 2026)
As cities account for over 70% of global energy-related carbon emissions, the community scale has emerged as a critical but undertheorized site for urban decarbonisation. Translating city-level net-zero commitments into verifiable outcomes requires disaggregation to the neighbourhood level, where energy use, mobility, governance, and social practice intersect most directly. Yet no systematic bibliometric mapping of the net-zero carbon community (NZCC) field currently exists. This review analyses 1,292 Scopus-indexed publications from 2001 to 2026, applying keyword co-occurrence network analysis, burst detection, geographic mapping, and spatial scale cross-tabulation to characterise the field’s structure and identify persistent gaps. Annual output has grown from fewer than 30 papers through 2019 to 375 in 2025, coinciding with the EU Green Deal and China’s dual-carbon pledge. Three structural deficits are found through the analysis, including marginalisation of governance studies, the unlinking of carbon assessment and governance literatures and the underrepresentation of developing countries. Advancing the field requires integrating institutional analysis with carbon assessment, building feedback loops between monitoring evidence and governance design, and developing context-sensitive frameworks for the Global South.